AIDS mortality and socioeconomic indexes in the city of Sao Paulo, 1994-2002 - Farias, Norma; Cardoso, Maria Regina A (Revista de Saúde Pública, 2005)
OBJECTIVE: To investigate the correlation between AIDS mortality rates and social inclusion/exclusion indexes among male and female populations aged between 25 to 49 years. METHODS: The study was carried out in 96 administrative districts of the municipality of São Paulo in the period 1994-2002. Mortality data were collected from the Program for Improving Local Mortality Data and from population estimates based on the 1991 and 2000 census of the State System Data Analysis (SEADE) Institute and the Municipal Department of Planning. The indicators were obtained from the city's map of exclusion (1996 and 2000). Statistical analysis was performed using Pearson's correlation test (at 5% level). RESULTS: A significant positive correlation was seen among men between AIDS mortality and the district life quality index from 1994 to 1998 (p